Analisis Struktur Mikro Wacana pada Iklan Sampo Lifebuoy - Gusti Ayu Putu Setiani; Anak Agung Putu Putra; Ni Putu N. Widarsini (Journal of Mandalika Literature, 2024)
The purpose of this study was to analyze Lifebuoy shampoo advertisements using van Dijk's critical discourse analysis model with the main focus being on microstructure. The approach applied in this study is the critical discourse analysis of van Dijk's model. Data collection techniques use free listening, transcription techniques, and screenshot techniques. The data analysis techniques used are certain element sorting techniques or called PUP and BUL techniques or called Direct Element Sharing. The results of the study include an in-depth understanding of microstructure that discusses syntax, semantics, stilistics, and rhetoric in Lifebuoy shampoo advertisements. Through this discourse analysis, you can find out in depth about the discussion in Lifebuoy shampoo advertisements.